Peer instruction como metodologia ativa para aprendizagem de cinemática no ensino remoto - Caetano, Kellen Cristine (2021)
Currently, much is discussed about the direction of education in times of pandemic. What are the consequences that remote education may have left on the quality of Brazilian education and what attitudes can be taken in order to reduce these impacts. Applying a teaching method, based on active methodologies, in the remote model seeks to attract and motivate young people to participate and commit to their educational process, also increasing their interest in physics and increasing their knowledge of physical concepts. The research was carried out with students from the first grade of a military school where two groups tried the Peer Instruction method of teaching and the other followed with traditional classes, all linked to the remote system with synchronous and asynchronous classes, focusing on the concepts of kinematics. The classes that tried the method were also able to have contact with a movement analysis program, called CVMob, in order to produce and analyze videos of different movements. At the end of the survey, the classes showed a very similar performance, as during the application of the educational product, students stopped actively participating in online classes or watching the recorded classes. Even with different approaches, classes deliver very similar results. It is therefore concluded that one of the main challenges of remote learning is the effective motivation of students. Contact with the teacher in the classroom was lacking for students who attended only asynchronous classes, with conceptual flaws in their speeches being perceived, different from those who attended synchronous classes. Even with the withdrawal of some during the course of classes, the experience of learning physics with different methods and experimenting with new technological resources was still valid.